Assessment of annual aggregate commercial energy loss due to day-on road lights: a field research study - Sadda Jayachandra; Shaik Rafikiran (Institute of Advanced Engineering and Science, 2026)
The electrical vitality utilization is at a quick rate as compared to its era driving towards the need for vitality reserve. Every nation is concerned about addressing the energy security issue and most of their attention during the past few years has been focused on the very essence of energy conservation opportunities. It is the responsibility of all the electricity consumers to ensure that no portion of electrical vitality gets wasted either hastily or intentionally. Unfortunately, as a result of day-on-road lights (DORL), electricity is being wasted in several villages and towns. This claim is validated through the performed field research (FR) presented in this manuscript. From the FR, it is inferred that approximately 13.2% of the total road lights were found turned-on during the day hours, resulting in an annual vitality loss of approximately 55.75 MWh. It is being wasted because of the mismanagement of switches and manmade errors; because of this, it forms a part of the overall commercial loss of 4.8 tonnes of oil equivalent (toe) and accounts for the release of about 47.4 tonnes of CO? (tCO2) emissions per annum. This paper presents on broad investigation on the FR performed to recognize a yearly total commercial misfortune of vitality with techno-commercial analysis.